If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -114 + 7x = -2x + 147 Reorder the terms: -114 + 7x = 147 + -2x Solving -114 + 7x = 147 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -114 + 7x + 2x = 147 + -2x + 2x Combine like terms: 7x + 2x = 9x -114 + 9x = 147 + -2x + 2x Combine like terms: -2x + 2x = 0 -114 + 9x = 147 + 0 -114 + 9x = 147 Add '114' to each side of the equation. -114 + 114 + 9x = 147 + 114 Combine like terms: -114 + 114 = 0 0 + 9x = 147 + 114 9x = 147 + 114 Combine like terms: 147 + 114 = 261 9x = 261 Divide each side by '9'. x = 29 Simplifying x = 29
| (v/8)-9=-13 | | -1/3-21/3 | | 5t(3-6t)= | | (v/8 | | X^3-2x=100 | | 35x^2-34x+8=0 | | 34=-2-x^2 | | 2w(4+3w)= | | 3+11=-2(6x-7) | | y(-5/3)=1 | | -5(0)+2x=-10 | | 9=38(3x+32) | | 5x-3=40x+4 | | 9 = 38(3x+32) | | 4x^2-7=15 | | -5(7+3m)=-140 | | 2x=6+2x | | 3x-12=3x+-3x | | 5(3x+6)=-49+19 | | 3p(3-2m)= | | 4k(3+2d)= | | 1/3x-1/4(0)=2 | | 2x+25=6x+33 | | 5/6+3j=-1/2 | | 3n^3/6n | | 16G^2-16G+3=0 | | 6/7y=30 | | -4x-2+7x=3x-2 | | (w+4)(w+5)=12 | | 3=1/2(3x-6) | | 6z-z=-2+3z-3-1 | | 1/3(0)-1/4y=2 |